2008
DOI: 10.1053/j.gastro.2008.05.053
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital-Acquired Infection on Outcome in Acute Pancreatitis

Abstract: We determined that HAI had a major impact on mortality in AP. Patients who developed HAI also had significantly increased LOS and hospital charges. These differences were not explained by increased disease severity alone. Reducing HAI is an important step to improving outcome in AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 28 publications
4
49
0
1
Order By: Relevance
“…The presence of extra-pancreatic infection was a risk factor for infected necrosis, and in 61% of cases with pancreatic infection, the same pathologic organism was isolated from pancreatic and extra-pancreatic tissue. In a separate study of 11,046 cases of acute pancreatitis from US hospitals, 15% of all fatal cases of acute pancreatitis were associated with hospital-acquired infection [20]. Extra-pancreatic infection was associated with a significantly increased mortality even after adjusting for disease severity.…”
Section: Infectionmentioning
confidence: 95%
“…The presence of extra-pancreatic infection was a risk factor for infected necrosis, and in 61% of cases with pancreatic infection, the same pathologic organism was isolated from pancreatic and extra-pancreatic tissue. In a separate study of 11,046 cases of acute pancreatitis from US hospitals, 15% of all fatal cases of acute pancreatitis were associated with hospital-acquired infection [20]. Extra-pancreatic infection was associated with a significantly increased mortality even after adjusting for disease severity.…”
Section: Infectionmentioning
confidence: 95%
“…As in other diseases, hospital-acquired infection leads to elevated costs. Wu and coworkers [2] reviewed more than 11,000 patients with acute pancreatitis and found that 0.7% developed a hospital-acquired (nosocomial) infection, which was associated with a 9-fold to 10-fold increase in mortality and a signifi cant increase in total costs.…”
Section: Introductionmentioning
confidence: 99%
“…Their infection tends to occur in 10-70% of cases with pancreatic necrosis and increases mortality (23). The distinction between sterile or infected collections is very important because they have different prognosis and treatment (24).…”
Section: Discussionmentioning
confidence: 99%